(untitled) (Cadernos ESP, 2022)
The objective of the study was to describe and analyze the sociodemographic characteristics and diseases of the ICD-10 chapters that caused infant deaths, calculate the infant mortality rate and its temporal trend and the chapter in which the highest number of these deaths occurred in the 7th Region of Health in the State of Ceará, from 2009 to 2019. A descriptive, ecological time series study was carried out. The data revealed a predominance of males with 60.51% of deaths, 62.56% of mixed race/color, 55.38% of low weight, 64% of deaths occurred at an early neonatal age and 60% were deaths from diseases belonging to Chapter XVI of the ICD-10. The average infant mortality rate for the years studied was lower than in Ceará, 11.70 and 13.02 per thousand inhabitants, respectively. Many of these deaths could be avoided in this region through the consolidation and strengthening of maternal and child care lines.